English Teacher’ Perceptions and Classroom Practices on Constructivism Values in Primary Schools in Badung Regency - Agustini, N.W. W. (Jurnal Pendidikan Bahasa Inggris Indonesia, 2019)
This study aimed at describing teachers' perceptions on the concept, implementation, and impact of constructivism values in public primary schools in Badung Regency; how the teachers practice and implement constructivism values in the classroom; and finding out the relation of teachers' perceptions about constructivism values and its practices in the classroom. This study was designed in the form of a mixed methods with the embedded design in which the quantitative data were more dominant than the qualitative data so that the data were described descriptively and quantitatively. The subjects of this study were three English teachers with the same qualifications of educational background (English Education) from three different public primary schools in Badung Regency. The data related to teachers’ perceptions were collected through questionnaire administration, the classroom practices and implementation were collected through classroom observations, and supported with interviews. After the data were collected, the data were analyzed quantitatively to analyze the results of the questionnaire, and qualitatively by using interactive analysis model to analyze the results of classroom observations and interviews. The results of the study indicated that: first, the teachers had strong perceptions on the concept, implementation, and impact of constructivism values; second, the frequency of occurrences on the practices of constructivism values in the classroom was categorized as low frequency which indicated that the teachers rarely practiced constructivism values in the classroom; third, since the teachers had strong perceptions on constructivism values but the frequency of the practices was categorized as low frequency. It could be concluded that the teachers tend to be inconsistent between their perceptions on constructivism values with its practices in the classroom